Electrochemical synthesis and corrosion protection properties of poly(o-toluidine) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2005)
Uniform and strongly adherent poly(o-toluidine) (POT) coatings have been synthesized on low carbon steel (LCS) substrates by electrochemical polymerization (ECP) of o-toluidine under cyclic voltammetric conditions from an aqueous sodium tartrate solution. Cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) measurements, and scanning electron microscopy (SEM) were used to characterize these coatings, which indicates that the sodium tartrate is a suitable medium for the ECP of o-toluidine and it occurs without noticeable dissolution of LCS. Corrosion protection properties of the POT coatings were evaluated in aqueous 3% NaCl by the potentiodynamic polarization measurements and CV. The result of the potentiodynamic polarization demonstrates that the POT coating has ability to protect the LCS against corrosion. The corrosion potential was about 334 mV more positive in aqueous 3% NaCl for the POT-coated LCS than that of bare LCS and reduces the corrosion rate of LCS almost by a factor of 50. (c) 2005 Wiley Periodicals, Inc.
Keywords: conducting polymers; Corrosion resistant coatings; cyclic voltarnmetry; Electrochemical polymerization; FT-IR; Poly(o-toluidine); UV-vis spectroscopy